Intellectualism of ABIM (Malaysian Islamic Youth Force): Ismail al-Faruqi's Perspective - Amir Ahmad Nabil; Tasnim Abdul Rahman (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
This study discusses the contribution and influence of al-Faruqi (1921-1986) to ABIM (Malaysian League of Muslim Youth). It seeks to see the impact of its modern and inclusive manhaj on ABIM's struggle and its relevance to society in Malaysia and the aspirations of contemporary da'wah. In his efforts to realize the ideals of Islamiyyah, al-Faruqi has exerted a great influence on the manhaj and ABIM's moderate and moderate approach. He has outlined significant philosophies and methodologies in his writings such as al-Tawhid: Its Implications for Thought and Life; Hijrah: The Necessity of its Iqamat or Vergegenwartigung; Islam; Islamization of Knowledge and Islam and Other Faith; and his translation of Syeikh Muhammad al-Ghazali's Our Beginning in Wisdom (Min Huna Na'lam) and Khalid M. Khalid's From Here We Start (Min Huna Nabda') which has shaped the moderate and progressive views of ABIM and had a profound impact that shaped weltanschauung its dynamic Islam. This study attempts to look at the role of al-Faruqi in shaping idealism and outlining the direction of the struggle and strengthening of ABIM da'wah and its impact on the school of thought, da'wah traditions, and civilizational dialogues that it champions.